Dancing in the Imagined Space of Music - Duerden, Rachel (Edinburgh: Edinburgh University Press, 2007)
RESUMEN: Dance and music have several features in common - rhythm, metre, tempo, and the fact that they are structured in and through time - but they are also intrinsically different, they each 'mean' differently, making the task of talking about their interrelationship challenging. Perhaps, however, this combination of closeness and distance is what makes it possible to see dance as a metaphor for music, and vice versa. The closeness between the two announces a relationship, a connection that then extends beyond the natural affinity to embrace something more remote and surprising. In other words, linking two disparate entities in a way similar to metaphor highlights a clear point of contact between them, but it also invites us to consider additional connections - the ghostly resonances that become apparent through close study. Through an analysis in which illustrations are drawn from Balanchine and Stravinsky's Agon (1957) and Mark Morris' Falling Down Stairs (1997) set to J. S. Bach's 3rd Suite for Cello, this article examines the use of metaphor in talking about our responses to dance and music, thus illuminating some of the potential for subtlety and depth in their relationship, and the corresponding insights into human experience that they may offer.